Opening and closing doors: The role of language in international opportunity recognition and exploitation. Issue 6 (December 2015) - Hurmerinta, Leila; Nummela, Niina; Paavilainen-Mäntymäki, Eriikka
Highlights Language skills of the decision-maker are related to international opportunity recognition and exploitation. Language skills may create a knowledge corridor, which either encourages or prevents the decision-maker from seeing a greater number of international opportunities. Matching linguistic knowledge helps managers to recognise international opportunities, especially if it is accompanied by language diversity and deeper culture-specific knowledge. The impact of the linguistic knowledge corridor has decreased due to the emergence of English as business language and digitalisation.